Technology mediated bilingual participatory culture framework for delivery of education for students: in disrupted or war zones - Randle, Oluwarotimi (Universitas Kanjuruhan Malang, 2024)
This paper aims to provides a perspective and framework for the utilization of technology mediated education as a tool for providing education to individuals whose education have been disrupted by civil war and unrest as a platform for participatory culture education through bilingualism. The study utilized an inductive content analysis through transformative paradigm to elicit critical points which would constitute as components of this conceptual article. The systematic review of literature was adopted through databases such as Google Scholar and ProQuest, this led to the development of categories and subcategories which were organized and identified through the utilization of thematic methods. The utilization of participatory culture through bilingualism will promote inclusive education and promote the acceptance of various forms of learning and various languages. A technology mediated bilingual participation culture policy will help students and learners in war affected zones.